[A, B] | = | AB - BA | (5.1) |
{A, B} | = | AB + BA | (5.2) |
![]() ![]() |
= | ![]() ![]() ![]() ![]() |
(5.3) |
![]() ![]() |
= | - ![]() ![]() |
(5.4) |
![]() ![]() |
= | A[B, C] + [A, C]B | (5.5) |
![]() ![]() |
= | B[A, C] + [A, B]C | (5.6) |
![]() ![]() ![]() ![]() |
= | {A,{B, C}} - {B,{A, C}} | (5.7) |
![]() ![]() |
= | AC[B, D] + A[B, C]D + C[A, D]B + [AC]DB | (5.8) |
![]() ![]() |
= | A{A, C}D - AC{B, D} - C{A, D}B + {C, A}DB | (5.9) |
eAt | = | ![]() ![]() |
(5.10) |
eAeB | = | eA + Be![]() |
(5.11) |